Pola Kemitraan Pemerintah dan Swasta dalam Kebijakan Reklamasi Pantai di Kota Makassar - Afni Amiruddin; Andi Samsu Alam (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
This study aims to identify and describe about the implementation of the partnership (cooperation) between the Government of South Sulawesi Province and the developer PT. Yasmin Bumi Asri regarding the realization of the coastal reclamation in Makassar along the factors that affect it. The results indicated: First, regarding the realization of the coastal reclamation in Makassar, the Government of South Sulawesi Province has involved the second party in the realization process which lies in the area of the Center Point of Indonesia (CPI). PT Yasmin Bumi Asri wil The construction of the Center Point Of Indonesia (CPI) is motivated by the national spatial plan based on the Government Regulation No. 26 of 2008. One of them is the Mamminasata area (Makassar, Maros, Sungguminasa, and Takalar). In the Division of land the Government will utilize the results of the reclamation of about 50.6 Ha and for the developers will utilize about 106.7 Ha. Second, the factors that influence the relationship of cooperation between the Government of the Province of South Sulawesi, along with developer in this case PT Yasmin Green Earth include supporters and restricting factors. Factor endowments of capital assistance and equipment namely, Government policy.